PENGEMBANGAN GAME EDUKASI UNTUK MATERI BANGUN DATAR MENGGUNAKAN LINTASAN BELAJAR GEOMETRI - Budhayanti, Clara Ika Sari; Bata, Julius (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Mathematics is an essential subject for students to master from the start. However, most students have difficulty learning mathematics and reduce interest in learning. This is one of the causes of low math test results. Therefore, a learning method or media was needed that can attract students' interest in learning. One of the learning media that can attract students' interest in educational games. This study aims to develop educational games that can be needed as a medium for learning mathematics, primarily material about geometry. The research method used in this research is development research. The geometry learning path is used as the basis for game design. The trial was conducted with a small group involving teachers and students. The game was developed using the Unity 3D game engine with a digital storytelling model in the geometry learning pathway in elementary schools. The results of the development show that the educational game with the name